Attention ! Un plurilinguisme peut en cacher un autre. Enjeux théoriques et didactiques de la notion de pluralité - Véronique Castellotti (Recherches en didactique des langues et des cultures)
Inspired by the various articles contributing to this issue, this paper develops an analysis of the stakes involving plurilingualism, as they have been construed within dominant language policies, primarily in Europe. I will examine the ways in which such policies have been interpreted in various research projects at the intersection of sociolinguistics and language didactics.